Prevalencia de dientes cariados perdidos y obturados (CPOD), en las estudiantes de sexo masculino de la Universidad Nacional de Loja Modalidad Presencial periodo mayo - julio del 2014. - Galindo Hernandez, Andrea Carolina (2014)
The present study was performed in order to determine the prevalence of decayed, missing and filled teeth (DMFT) among students of 18-30 years old male from the National University of Loja. The universe used were 894 students in the classroom mode, from which a sample of 442 male students aged 18 and under 30 was taken. This study is a descriptive transversal. To obtain data dental history was used. The results showed that students of 18-30 years have a group DMFT of 9.4 which corresponds to a very high level of risk. The prevalence of decayed teeth in students 18 to 24 years is 81% higher than this being students of 25-30 years, which is 79%. The prevalence of missing teeth according to age groups is 41% for students of 18 to 24 years which is lower than students of 25 to 30 years in which is 71%. The prevalence of filled teeth is 73% in students of 18 to 24 years and 76% for students between 25 to 30 years. Keywords: dental caries, tooth loss, filled teeth, DMFT.